(untitled) (Journal of Engineering, 2023)
...... The Iraqi government seeks to overcome the financial crisis by investing and privatizing some projects to achieve sustainable growth. Most of the investment projects in Iraq suffer from many constraints that greatly impact the success of these projects. A survey of the opinions of a group of experts was conducted to identify the most important constraints facing the investment process in Iraq. Then the experts’ answers were arranged in a closed questionnaire and distributed to the research sample for which the statistical analysis was conducted. Through it, the most important (17) factors that had the greatest impact on the failure of investment projects in Iraq were reached. One of the main constraints was the slow and routine administrative procedures. Therefore, the main objective of the research is to identify the most important constraints facing the investment process in Iraq and to develop a proposed system to organize the procedures for applying for investment opportunities, given the importance of long-term investment, the importance of the referral stage, and the selection of the competent investor who meets the criteria required for the success of the investment project. The researcher concluded that many factors impact the failure of investment projects, which must be addressed for the success of these projects, as management systems and computer technology programs greatly organize investment procedures, save time and reduce routine and slow procedures.